Farmer Insights Regarding Zero Tillage Systems Against Weeds in the Eastern Gangetic Plains of South Asia: Farmer insights regarding zero tillage systems against weeds - Suri, Bhavya; Timsina, Pragya; Chaudhary, Anjana; Karki, Emma; Sharma, Akriti; Sharma, Rama; Gartaula, Hom Nath; Brown, Brendan (South Asian Journal of Agriculture, 2023)
A large amount of literature has now proven that Zero Tillage (ZT) as a part of Conservation Agriculture-based Sustainable Intensification (CASI) practices has the potential to help smallholder farmers in the Eastern Gangetic Plains (EGP) of South Asia transition to more productive, profitable, and sustainable production systems. Despite this, changes in weed management under ZT are commonly identified as a constraint to wider adoption, based primarily on quantitative investigations. Yet the contribution of this to farmers’ evaluation and adoption behaviour remains underexplored. To address this issue, we explore farmers’ perceptions of CASI-based herbicide weed management systems using semi-structured interviews from six locations across the EGP. This study identifies a divergence in experiences with herbicides, both geographically (with Sunsari and Bihar more negative than other locations) and in terms of user typologies (where users are overwhelmingly positive, and non-users are overwhelmingly negative). This divergence suggests that an information void exists that has the potential to contribute strongly to the negative evaluation of CASI, as well as potentially negative changes in household labour dynamics. To overcome this, promotional efforts should target education and training programs that address how to effectively spray, potentially with increased emphasis on use of weather forecasting. This would ensure equitable outcomes for household members, and increased interest and use of CASI could be promoted. South Asian J. Agric., Vol. 9, No.1&2, 2022-‘23: 52-63